Pengaruh Ukuran Perusahaan, Profitabilitas, dan Likuiditas terhadap Opini Audit Going Concern : Studi Kasus pada Perusahaan Sektor Consumer Non Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Nanda Suci Handayani Umagap; Mulyadi Mulyadi; Elia Rossa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze and examine the influence of company size, profitability, and liquidity on going-concern audit opinions in companies listed on the Indonesia Stock Exchange (IDX). Going-concern audit opinions are important indicators provided by auditors to assess the company's future business continuity. Factors such as company size, profitability, and liquidity are often associated with the auditor's likelihood of issuing such an opinion. The research method used is a quantitative method with an associative approach. The types and sources of data used in this study are secondary data in the form of annual financial reports of companies listed on the IDX during the 2019–2023 period. Sampling was carried out using a purposive sampling method, namely determining samples based on certain criteria relevant to the research objectives. From this process, 375 observational data samples were obtained. Data processing and analysis were carried out using IBM SPSS (Statistical Product and Service Solutions) version 27 software, which allows for accurate and measurable statistical testing. The results of the study indicate that company size does not affect going-concern audit opinions, so the size of the company's assets is not a determining factor for auditors in issuing such an opinion. Meanwhile, profitability was shown to have a significant influence on going-concern audit opinions, with companies with higher profitability tending to receive unmodified going-concern audit opinions. Conversely, liquidity had no effect on going-concern audit opinions, indicating that the ability to meet short-term obligations is not always a primary consideration for auditors. These findings are expected to contribute to company management, auditors, and investors' understanding of the factors influencing going-concern audit opinions.